Healing spaces as a design approach to optimize emotional regulation for patients with mood disorders - Yan, Shuaijie; Azmi, Athira; Mansor, Noranita; Wang, Zhihao (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Healing spaces have played an important role in human history as arenas for healing and restoration of physical health. Current research from across disciplines identifies that engagement with space for people with mental illness can reduce emotional stress and thus improve health. This research leads to the central question of this paper: How do people with mood disorders achieve emotional regulation through healing spaces? In response to this question, this paper investigates the effects of sensory experience and architectural space on emotion regulation, with a particular focus on healing spaces. It proposes a model to analyze and explain how the design and use of healing spaces can create emotional experiences that stimulate patients’ senses and facilitate emotional regulation in individuals with mood disorders. The study emphasizes the importance of understanding how elements of healing spaces affect patients’ senses and contribute to the quality of emotion regulation. The paper argues that healing structures can effectively enhance the emotional experience of a space by creating a positive spatial atmosphere, thereby aiding in the healing process for patients with mood disorders. This paper’s analysis of the existing literature identifies key mechanisms by which healing spaces promote emotion regulation-healing structures-and breaks them down into three main structures: (a) Safety Guarantees Physical and Mental Development; (b) Functionality Supports the Treatment Process; (c) Ambiance Promotes Emotional Comfort, this study examines existing evidence to determine how healing structures promote emotionally regulated treatment. The study also explores representative examples of healing spaces and how they utilize spatial elements to stimulate the patient’s senses. This research results show that healing structures directly influence or facilitate eight primary spatial elements (color and form, light, sound, air and temperature, nature, materials, play and games, and activity and communication) which incorporate one or more dimensions of healing. Therefore, this paper aims to enhance our understanding and awareness of the correlation between interior space, human senses, and healing structures.